(untitled) (Philological Studies, 2019)
The subject of this paper is the manuscripts from XII to XVI century that belong to Macedonian provenience. These manuscripts represent the main corpus for the dictionary of Church Slavonic of the Macedonian provenience. The basic norms in the Macedonian provenience of Church Slavonic were first established at the end of the XI century to be fully developed during the XII century. The texts of the Macedonian provenience contain interesting orthographic and phonetic characteristics that resulted from the interplay of two factors: the important influence of the Ohrid Literary School and extensive relations among various proveniences. In addition, the copyists of those manuscripts were not isolated neither from the influence of their dialects, not from the influence of the original manuscripts.